A new ecological index for the status of mesophotic megabenthic assemblages in the mediterranean based on ROV photography and video footage. (15th June 2016) - Cánovas-Molina, Almudena; Montefalcone, Monica; Bavestrello, Giorgio; Cau, Angelo; Bianchi, Carlo Nike; Morri, Carla; Canese, Simonepietro; Bo, Marzia
Abstract: A new index of ecological status, named Mesophotic Assemblages Ecological Status (MAES) index, was elaborated on the basis of ROV (Remotely Operated Vehicle) photography and video footage in order to assess the status of mesophotic megabenthic assemblages from hard bottom. The index was tested on seven sites located between 50 and 150 m depth in the Ligurian and Tyrrhenian seas (western Mediterranean Sea). The MAES index considers three main parameters: (i) the community structure (number of megabenthic taxa, percent biotic cover in the basal layer, density of erect species); (ii) the condition of the dominant erect species (average height, percent of colonies with epibiosis/necrosis); (iii) the visible human impact (density of marine litter, including lost fishing gears). Two versions of the index have been elaborated, the complete version (MAES) and the quick version ( q -MAES), which showed comparable results, therefore suggesting the possibility of fastening assessment times. The sensitivity of the MAES index was correlated with the putative human pressure acting upon the site (semi-quantitatively assessed considering fishing effort and coastal urbanization). A standard working protocol related to the evaluation of the MAES index is here proposed with the intent to create an effective monitoring tool for the assessment of the ecological status of mesophotic assemblages on a large scale, as required by the EU Marine Strategy Framework Directive. MAES index will enhance the comprehension of the dynamics of mesophotic Mediterranean megabenthic assemblages with respect to human pressures and will also provide marine scientists and managers with a valuable tool specifically designed for the conservation of such vulnerable marine ecosystems. Highlights: We proposed MAES index to assess the ecological status of mesophotic assemblages. Sampling was conducted by means of ROV photography and video footage. The index was tested in western Mediterranean Sea. MAES index showed to be sensitive to the level of pressure.